Vitamin D metabolism in the fruit bat (Rousettus aegyptiacus) - Cavaleros, Meropi (My University, 1992)
Rouesettus aegyptiacus, the fruit bat is a crepuscular frugivore with no obvious access to either exogenous or endogenous sources of vitamin D. Therefore this animal's vitamin D status and endocrine system was investigated. Both captive and wild populations of fruit bats appear to be naturally in a vitamin D impoverished state. The serum concentration of the principle circulatory, metabolite [25(OH)D] is undetectable (< 4 ng/ml), Fruit bats possess the full compliment of enzymes associated with the vitamin D endocrine system. This was shown when labelled more polar metabolites were produced after the administration of 3H vitamin D3 and 3H 2S(OH)D3' Furthermore, a specific vitamin D binding protein (DBP) is present. After partial purification, it was revealed that this molecule is slightly larger in molecular mass than that of humans and baboons. The intraperitoneal administration of 25(OH)D3 revealed enhanced 1a-hydroxylase activity such that 1.7 times more 1,25(OH)2Ds was produced than 24,25(OH)2D3' The ratio of these di-hydroxylated metabolites conform with the ratio of these 2 metabolites in states of vitamin D deficiency and thus confirm the impoverished vitamin D status. Undetectable serum concentrations of 25(OH)D3 might therefore be explained by a limited exogenous vitamin D substrate (rotting fruit peels and fungi). Given the elevated 1a hydroxylase activity 1 the small amount'S of 25(OH)D produced would be rapidly converted to the active metabolite. The low concentration of active hormone appear adequate for the maintenance of mineral homeostasis as indicated by tightly controlled serum calcium (2.26 ± 0.17 mrnol/l), magnesium 01.16 + 0.24 mmol/l) and inorganic phosphorus (2.93 ± 1.01 mmol/I). Both vitamin D2 and vitamin D3 metabolites were detected in bat serum albeit in very small amounts, suggesting that fruit bats exploit both exogenous plant sources (skins of fruit - vitamin 1)2; fungi - vitamin D:3)and might indeed receive some U. V. light during their crepuscular forays to endogenously produce small amounts of vitamin D3 In conclusion, fruit bats appear to belong to a small group of animals that naturally have limited access to Vitamin D, yet the vitamin D endocrine system in these animals is no different to that of other mammals. These animals have adapted their vitamin D endocrine system to function well at the low hormone concentrations and they exhibit no pathological problems associated with relative vitamin D depletion.
A dissertation submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg for the Degree of Masters of Science. December 1992.
Keywords: Vitamin D